Analisis Persediaan Bahan Baku Kedelai Menggunakan Metode EOQ pada Industri Rumahan Keripik Tempe Memey - Aprilian, Wiko Ekasurya; Marliani, Sari; Yuliawati, July (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This research aims to find the best way to manage raw material supplies in the Memey Tempe Chips Home Industry, Karyasari Village, Rengasdengklok, Karawang. This research uses a descriptive method with a quantitative approach, collecting data through observation, interviews, and documentation. The data used comes from the period March 2022 to February 2023. The research results show the difference between the inventory control method used by the company and the EOQ method. The company's policy results in an order quantity of raw materials of 20 Kg, order frequency of 180 times, safety stock of 10 Kg, and reorder point of 20 Kg with a total inventory cost of IDR 1,050,040. Meanwhile, using the EOQ method produces a raw material order quantity of 277 Kg, order frequency of 13 times, safety stock of 20 Kg, and reorder point of 30 Kg with a total inventory cost of IDR 134,182. The difference in comparison between the company's method and the EOQ and POQ methods is that the raw material order quantity is 257 Kg, the order frequency is 167 times, the safety stock is 10 Kg, the reorder point is 10 Kg, and the total inventory cost is IDR. 915.858